1992
DOI: 10.1159/000116817
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Storage Myopathy in Multiple Acyl-CoA Dehydrogenase Deficiency: An Adult Case

Abstract: A 25-year-old woman had been complaining of episodes of muscle weakness, nausea and vomiting since the age of 10. Muscle biopsy showed free fatty acid accumulation and mitochondrial abnormalities. Mitochondrial DNA appeared to be normal at Southern analysis. Biochemical investigations demonstrated: glutaric aciduria type II, decreased levels of carnitine in liver and values at the lower level of normal in muscle, increased muscle carnitine palmitoyl transferase activity, partial cytochrome c oxidase and succin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…40 mg (A) or 10 mg (B) of protein was loaded per lane in a 4^15% HCL SDS-PAGE gel. The bands were visualized using a phosphor imager (STORM 840, Molecular Dynamics) dehydrogenase deficiency, long-chain L-3-hydroxyacyl-CoA dehydrogenase deficiency and short-chain acyl-CoA dehydrogenase deficiency (reviewed in Cwik 2000), and in an increasing number of patients with MADD (summarized in Antozzi et al 1994;Mongini et al 1992). In three of these cases, decreased ETFQO activity has been demonstrated (Bell et al 1990;DiDonato et al 1986;Loehr et al 1990) and one patient was shown to be compound heterozygous for a defect in the ETFDH gene (genotype [245C>T/S82F] þ [652G>A/D218N]) (Goodman et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 mg (A) or 10 mg (B) of protein was loaded per lane in a 4^15% HCL SDS-PAGE gel. The bands were visualized using a phosphor imager (STORM 840, Molecular Dynamics) dehydrogenase deficiency, long-chain L-3-hydroxyacyl-CoA dehydrogenase deficiency and short-chain acyl-CoA dehydrogenase deficiency (reviewed in Cwik 2000), and in an increasing number of patients with MADD (summarized in Antozzi et al 1994;Mongini et al 1992). In three of these cases, decreased ETFQO activity has been demonstrated (Bell et al 1990;DiDonato et al 1986;Loehr et al 1990) and one patient was shown to be compound heterozygous for a defect in the ETFDH gene (genotype [245C>T/S82F] þ [652G>A/D218N]) (Goodman et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of MADD patients with this phenotype, however, the primary defect has not been elucidated. The patients often respond to pharmacological doses of riboflavin, and since riboflavin is the precursor of FAD, the obligate coenzyme for ETF and its substrates, it has been suggested that these patients have a primary defect related to mitochondrial FAD metabolism (Antozzi et al 1994;Mongini et al 1992;Vergani et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…These patients may present anytime during infancy to adulthood, with recurrent episodes of lethargy, vomiting, proximal muscle weakness, hypoglycemia, metabolic acidosis, hepatomegaly and encephalopathy during metabolic stress (Mongini et al 1992;Beresford et al 2006;Liang et al 2009). These episodes may be lethal (Angle and Burton 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Children in this group usually develop severe cardiomyopathy and die during the first few weeks of life (1). The course and presentation of the late-onset patients is extremely variable, ranging from episodes of vomiting with hypoglycemia and hepatomegaly to progressive lipid storage myopathy in adulthood (3)(4)(5).…”
mentioning
confidence: 99%